2016
DOI: 10.1590/s1677-5538.ibju.2014.0465
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin determined at emergency department as an early indicator of progression to septic shock in patient with sepsis associated with ureteral calculi

Abstract: Introduction:To investigate the role of initial procalcitonin (PCT) level as an early predictor of septic shock for the patient with sepsis induced by acute pyelonephritis (APN) secondary to ureteral calculi.Materials and Methods:The data from 49 consecutive patients who met criteria of sepsis due to APN following ureteral stone were collected and divided into two groups: with (n=15) or without (n=34) septic shock. The clinical variables including PCT level for this outcome were retrospectively compared by uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
2
15
1
2
Order By: Relevance
“…Previous studies have demonstrated that 26-33% of patients with bacteremic UTI present with uroseptic shock (32, 33) (35.2% in Taiwan) (34). Moreover, consistent with the present study, Ko et al indicated that higher bacteremia rates were observed in patients with uroseptic shock induced by urolithiasis-related acute pyelonephritis (35), and bacteremia was identified as an independent risk factor for septic shock in patients with acute obstructive pyelonephritis (36). Consequently, prolonged duration of antibiotic therapy should be considered in diabetic patients with bacteremic UTI and in patientswith septic shock due to the existence of bacteremia accompanied with more serious manifestations.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that 26-33% of patients with bacteremic UTI present with uroseptic shock (32, 33) (35.2% in Taiwan) (34). Moreover, consistent with the present study, Ko et al indicated that higher bacteremia rates were observed in patients with uroseptic shock induced by urolithiasis-related acute pyelonephritis (35), and bacteremia was identified as an independent risk factor for septic shock in patients with acute obstructive pyelonephritis (36). Consequently, prolonged duration of antibiotic therapy should be considered in diabetic patients with bacteremic UTI and in patientswith septic shock due to the existence of bacteremia accompanied with more serious manifestations.…”
Section: Discussionsupporting
confidence: 90%
“…Study of Young et al [ 31 ] evaluated the ability of PCT as an early detector of septic shock in patients with acute pyelonephritis secondary to ureteral calculi. They considered 49 patients and divided them into 2 groups: with and without septic shock.…”
Section: Procalcitonin As Diagnostic Toolmentioning
confidence: 99%
“…Obtaining PCT might also be a useful prognostic tool. Although a single value PCT does not correlate well with severity of sepsis, mortality or outcome in ED patients with pyelonephritis [ 46 , 47 ], initial PCT levels are a predictor of progression to septic shock in patients with acute pyelonephritis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%